ANALISIS GAYA HIDUP DAN ETNOSENTRISME KONSUMEN TERHADAP PERSEPRI KUALITAS SERTA IMPLIKASINYA TERHADAP NIAT BELI KONSUMEN (STUDI KASUS PADA PENGGUNA SMARTPHONE SMARTFREN ANDROMAS PENGUNJUNG ITC ROXY MAS JAKARTA) - Wahyu Murti; Dreko Fernandez (Fakultas Ekonomi Universitas Borobudur, 2019)
This study aims to determine the extent of the influence of lifestyle and ethnocentrism ofconsumers on the perception of quality and its implications for the purchase intention ofSmartfren Andromax smartphones to ITC Roxy Mas Jakarta visitors.The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 100 people. Data processing method uses the path analysismethod (Path Analysis) with the help of SPSS version 23.0. Statistical testing uses the individualparameter significance test (t test) and simultaneous significance test (F test).The results showed that simultaneously Lifestyle variables, Consumer Ethnocentrism andQuality Perception significantly influence Work Productivity. Partially shows that analysis, 1:Lifestyle variables significantly influence Purchase Intention, whereas analysis, 2: ConsumerEthnocentrism variables significantly influence Purchase Intention and on the analysis,3: QualityPerception variable has a significant effect on Consumer Purchase Intention.Keywords: Lifestyle, Consumer Ethnocentrism, Quality Perception and Intention to Buy